Does reducing air pollution improve the progress of sustainable development in China?. (1st November 2020) - Zhao, Yuan; Tan, Ya; Feng, Shilan
Abstract: Understanding the extent to which air pollution influences the process of attaining sustainable development goals (SDGs) may help to estimate the benefit of reducing air pollution for improving sustainable development and to evaluate the necessity and urgency of reducing air pollutants and improving air quality. In this paper, we use the latest calculation of the SDGs in China to construct provincial panel data and investigate the relationship between air pollution and Chinese SDGs. We find that reducing air pollution will not only improve the SDGs directly associated with the environment, such as SDG3 (good health and well-being) and SDG15 (life on land), but also has a close relationship with the SDGs of other dimensions, such as SDG4 (quality education), SDG9 (industrial, innovation and infrastructure), SDG12(responsible consumption and production), SDG16 (peace, justice and strong institutions), SDG17(global partnerships). Based on the actual reduction in industrial SO2 emissions and evolution of the SDGs in China, we estimate that the former contributes approximately 3.5%–12.3% of the actual change in these SDGs from 2005 to 2015. Our findings support that reducing air pollution benefits the progress of sustainable development in various ways, and the efforts of curbing air pollution and improving air quality are especially valuable for sustainable development.